IMPLEMENTASI MEDIA PEMBELAJARAN PREZI TERHADAP HASIL BELAJAR MATERI PEDULI LINGKUNGAN PADA KEGIATAN KAMPUS MERDEKA DI SEKOLAH DASAR ISLAM PERMATA NUSANTARA - Zulfitria Zulfitria; Syafia Qatrunnada; Zainal Arif (Universitas Muhammadiyah Tangerang, 2022)
The purpose of this study was to determine the implementation of Prezi learning media on the learning outcomes of fourth grade students of Permata Nusantara Islamic Elementary School. This research was conducted at SD Islam Permata Nusantara involving 20 students. The research method used for data collection in this research is the technique of measuring learning outcomes data obtained through tests. The tests carried out in this study consisted of two tests, namely the Pre Test and Post Test. The results obtained after using Prezi learning media have a positive effect on student learning outcomes. This is evidenced by the results of the post test obtained by students, namely most students get a score of 70-80 in the category of good learning outcomes. So that the prezi learning media can improve the learning outcomes of fourth grade students with environmental care materials at SD Islam Permata Nusantara.